2018
DOI: 10.14411/eje.2018.022
|View full text |Cite
|
Sign up to set email alerts
|

Functional responses and intraspecific competition in the ladybird Harmonia axyridis (Coleoptera: Coccinellidae) provided with Melanaphis sacchari (Homoptera: Aphididae) as prey

Abstract: http://www.eje.cz plant growth correlated with the sticky "honeydew" covering the plant. Melanaphis sacchari transmits the sugarcane yellow leaf virus causing a 25% reduction in sugarcane yields (Akbar et al., 2010). Control of M. sacchari is diffi cult as pesticides cannot penetrate the greater canopy of sorghum. Pre-and post-harvest restrictions exacerbate the challenge of pesticide use (Armstrong et al., 2016). Melanaphis sacchari cannot destroy sorghum in a short term period, but the large populations grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…The expected increase in metabolic rates with warming are associated with greater energy demands, which should cause predators to increase food intake and foraging activity. Determining these parameters with respect to phenological stage confirmed poor response by the first three instars as reported earlier 59 , 74 , whereas increased foraging performance by final instar and adult H. axyridis (especially female when compared with male) 24 , 45 , 52 suggesting H. axyridis may provide better biocontrol efficiency at later stages, plausibly owing to better searching efficiencies. The 4th instar requires large meals to attain the required weight for pupation 75 and adult predators have to prepare for reproduction 56 and other functions related to egg maturation or fertilization 76 .…”
Section: Discussionsupporting
confidence: 77%
“…The expected increase in metabolic rates with warming are associated with greater energy demands, which should cause predators to increase food intake and foraging activity. Determining these parameters with respect to phenological stage confirmed poor response by the first three instars as reported earlier 59 , 74 , whereas increased foraging performance by final instar and adult H. axyridis (especially female when compared with male) 24 , 45 , 52 suggesting H. axyridis may provide better biocontrol efficiency at later stages, plausibly owing to better searching efficiencies. The 4th instar requires large meals to attain the required weight for pupation 75 and adult predators have to prepare for reproduction 56 and other functions related to egg maturation or fertilization 76 .…”
Section: Discussionsupporting
confidence: 77%
“…Functional response is an imperative criterion for assessing the efficiency of a predator on a given prey. Predation by H. axyridis using functional response experiments has been investigated against many crop pests [ 63 , 64 ]. However, no prior study reports predatory potential on S. litura eggs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 ], Aphis craccivora K. [ 67 ], Schizaphis graminum R. [ 68 ], Lipaphis erysimi K. [ 52 ], Myzus persicae S. [ 69 ], Myzus nicotianae S. [ 70 ], Rhopalosiphum nymphaeae L. [ 50 ], Melanaphis sacchari Z. [ 63 ] (Hemiptera: Aphididae) and eggs of Danaus plexippus L. (Lepidoptera: Nymphlidae) [ 49 ]. In our findings, temperature affected the magnitude of the egg predation by various stages of predator.…”
Section: Discussionmentioning
confidence: 99%
“…aphid) species. Previous literature has suggested that the invasive H. axyridis is an efficient predator of aphid pests (Xue et al 2009;Abbott et al 2014;Wu et al 2018) and this is likely to have facilitated the species' spread following multiple Functional response parameters were calculated through the fitting of the Rogers' 'random predator' type II functional response equation (Eq. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these species are historically common in the UK. The predatory ability of H. axyridis is believed to have been instrumental in the population declines of native Coccinellidae whilst giving the invasive species a competitive advantage, therefore facilitating its continued spread (for example Majerus et al 2006;Xue et al 2009;Abbott et al 2014;Wu et al 2018). Harmonia axyridis has been described as a voracious aphid predator (Majerus et al 2006), however, the impacts on prey populations within the invaded range are less studied (Roy and Brown 2015;Roy et al 2016a).…”
Section: Introductionmentioning
confidence: 99%